Unprecedented Noncanonical Features of the Nonlinear Nonribosomal Peptide Synthetase Assembly Line for WS9326A Biosynthesis. (17th June 2021) - Kim, Myoun‐Su; Bae, Munhyung; Jung, Ye‐Eun; Kim, Jung Min; Hwang, Sunghoon; Song, Myoung Chong; Ban, Yeon Hee; Bae, Eun Seo; Hong, Suckchang; Lee, Sang Kook; Cha, Sun‐Shin; Oh, Dong‐Chan; et al.
Abstract: Systematic inactivation of nonribosomal peptide synthetase (NRPS) domains and translocation of the thioesterase (TE) domain revealed several unprecedented nonlinear NRPS assembly processes during the biosynthesis of the cyclodepsipeptide WS9326A in Streptomyces sp. SNM55. First, two sets of type ΙΙ TE (TEΙΙ)‐like enzymes mediate the shuttling of activated amino acids between two sets of stand‐alone adenylation (A)‐thiolation (T) didomain modules and an "A‐less" condensation (C)‐T module with distinctive specificities and flexibilities. This was confirmed by the elucidation of the affinities of the A‐T didomains for the TEΙΙs and its structure. Second, the C‐T didomain module operates iteratively and independently from other modules in the same protein to catalyze two chain elongation cycles. Third, this biosynthetic pathway includes the first example of module skipping, where the interpolated C and T domains are required for chain transfer. Abstract : Systematic manipulation of the nonribosomal peptide synthetase (NRPS) domains in combination with elucidation of the interactions between the unique domains and structure revealed several hitherto unprecedented nonlinear NRPS assembly processes during the biosynthesis of cyclodepsipeptide WS9326A.